2013
DOI: 10.1093/mutage/ges076
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus induction in the bone marrow of rats by pharmacological mechanisms. I: glucocorticoid receptor agonism

Abstract: A novel selective glucocorticoid receptor (GR) agonist, AZD2906, was found to increase the incidence of micronucleated immature erythrocytes (MIE) in the bone marrow of rats given two oral doses at the maximum tolerated level. Because GR agonists as a class are considered not to be genotoxic and AZD2906 showed no activity in the standard in vitro tests or in vivo in a rat liver comet assay, investigative studies were performed to compare AZD2906 with a reference traditional GR agonist, prednisolone. Emphasis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Thus, the administration of some antibiotics (fluoroquinolone and macrolides), corticosteroids, anticoagulant, and antiviral agents has been shown to increase the level of DNA damage in COVID-19 patients. This is in line with the available literature data about genotoxic effects of certain medications like erythromycin and/or lincomycin [ 55 ], metronidazole and dimetridazole [ 56 ], and glucocorticoid receptor agonists [ 57 ]. Likewice, our results correspond to previously conducted studies related to genotoxic potential of oral anticoagulant [ 58 ] and antiviral [ 59 ] therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the administration of some antibiotics (fluoroquinolone and macrolides), corticosteroids, anticoagulant, and antiviral agents has been shown to increase the level of DNA damage in COVID-19 patients. This is in line with the available literature data about genotoxic effects of certain medications like erythromycin and/or lincomycin [ 55 ], metronidazole and dimetridazole [ 56 ], and glucocorticoid receptor agonists [ 57 ]. Likewice, our results correspond to previously conducted studies related to genotoxic potential of oral anticoagulant [ 58 ] and antiviral [ 59 ] therapy.…”
Section: Discussionsupporting
confidence: 88%
“…The animal data for prednisolone used for comparison to in vitro data in the current study were previously obtained in accordance with ARRIVE guidelines as described in Hayes et al 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The animal data for AZ12785452 used for comparison to in vitro data in the current study were previously obtained in accordance with ARRIVE guidelines using the study design outlined in Hayes et al 3 except that animals were killed by administration of isoflurane followed by severance of major blood vessels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now evidence that not all in vivo positive results are due to genotoxicity, and sustained changes in core body temperature, increased erythropoiesis, or decreased protein synthesis induced by test agents have all been shown to increase the frequency of micronucleated immature erythrocytes (MIEs). 6 More recently it has also been shown that increased MIE numbers in rat bone marrow can be a consequence of the pharmacological action of glucocorticoid receptor agonists 7 and long-acting β-2 agonism. 8 It is important to understand whether or not increases in MIE are due to geno-toxicity because, in the absence of a plausible non-genotoxic mechanism, a positive micronucleus test result is taken to indicate potential rodent carcinogenicity by regulators.…”
Section: Introductionmentioning
confidence: 99%